Kebebasan Beragama dalam Tinjauan Ensiklik Pacem In Terris - Jenny Fransisca Datu; Teresia Noiman Derung (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
Freedom of religion is a fundamental and internationally recognized human right, serving as an important foundation in creating a just society. This article explores religious freedom through the perspective of the encyclical Pacem in Terris issued by Pope John XXIII in 1963. In the document, the Pope affirms the right of every individual to worship God according to his conscience, both in private and in public. Although this freedom is guaranteed by the Indonesian constitution, its implementation often faces serious challenges such as intolerance and discrimination against minority groups. This article aims to examine the concept of religious freedom in the context of Pacem in Terris , focusing on articles 14, 35 and 36 of the encyclical, and its relevance to the current socio-political situation. Through an in-depth textual analysis of the encyclical and related literature, this article shows that the teachings of Pope John XXIII can serve as a guideline for strengthening tolerance and mutual respect among religious communities in Indonesia. Thus, this study is expected to contribute to a deeper understanding of religious freedom as part of human rights and the role of the state in ensuring its implementation.